Profesionalisme Chef Dalam Pengolahan Dan Meningkatkan Kualitas Makanan Di Cavinton Hotel Yogyakarta - T. Prasetyo Hadi Atmoko; Hery Krestanto - AKPAR Yogyakarta (Universitas Bina Sarana Informatika, 2017)
Abstract - The increasingly fierce competition of hotels encourages the hospitality industry in Yogyakarta to improve the quality of service, both room service and food and beverages. Chef Cavinton Hotel Yogyakarta in the face of competition is required to be able to commit and work with professionals in accordance with the correct food processing procedures, ranging from preparing and selecting the best materials, processing the material with the techniques and cooking the correct method, the processing of diverse foods, and presents with an attractive appearance, so that every food to be processed, processed and produced really has a good quality of food. This research uses qualitative descriptive method. The results of this study are employees of FB departments Cavinton Hotel Yogyakarta implement Standard Operation Procedure (SOP) in carrying out its work, food processing at Cavinton Hotel Yogyakarta According to Minister of Health Regulation No. 1096 / MENKES / PER / VI / 2011.Keywords : Chef Professionalism, Processing, Food Quality. Abstrak - Persaingan hotel yang semakin ketat mendorong industri perhotelan di Yogyakarta untuk meningkatkan kualitas pelayanan, baik pelayanan kamar maupun makanan dan minuman. Chef Cavinton Hotel Yogyakarta dalam menghadapi persaingan tersebut dituntut mampu berkomitmen dan bekerja dengan profesional sesuai dengan prosedur pengolahan makanan yang benar, mulai dari mempersiapkan dan memilih bahan yang terbaik, mengolah bahan tersebut dengan teknik dan cooking methode yang benar, pengolahan makanan yang beragam, serta menyajikan dengan penampilan yang menarik, sehingga setiap makanan yang akan diproses, diolah dan dihasilkan benar-benar memiliki kualitas makanan yang baik. Penelitian ini mengunakan metode deskriptif kualitatif. hasil penelitian ini adalah karyawan FB departemen Cavinton Hotel Yogyakarta melaksanakan Standard Operation Procedure (SOP) dalam melaksanakan pekerjaannya, pengolahan makanan di Cavinton Hotel Yogyakarta Sesuai Peraturan Menteri Kesehatan RI Nomor 1096/MENKES/PER/VI/2011.Kata Kunci : Profesionalisme Chef, Pengolahan, Kualitas makanan.